Pengaruh Strategi Experiential Marketing Terhadap Kepuasan Pengunjung Museum Sepuluh Nopember Surabaya - Dewi Ayu Miftahul Jannah; Nurita Andriani; Mohammad Arief (Jurnal Studi Manajemen dan Bisnis, 2014)
Surabaya, as a heroic city, saves a lot of history about war in independence era. It influences the creation of tourist objects in history nuance such as museum. Phenomenon on reality shows the opposite that people prefer to visit, even spending time in malls, theaters, and cafes than visiting a museum. So, it needs an effort to shift people preference by implementing Experiential Marketing strategy. The purpose of this study is to determine the effect of Experiential Marketing variables that consist of Sense Experience, Feel Experience, Think Experience, Act Experience, and Relate Experience on Sepuluh November Museum visitors’ satisfaction and also to determine the five elements of Experiential Marketing variable that dominantly influences the visitor satisfaction of Sepuluh November Museum Surabaya. This study applies quantitative methods with type of survey research conducted through structured interviews and questionnaires to 60 respondents, i.e visitors of Sepuluh November Museum Surabaya. The sampling technique used is purposive sampling technique, and is being analyzed through multiple regression analysis. The results of this study are (1) variable Sense Experience, Feel Experience, Think Experience, Act Experience, and Relate Experience jointly or simultaneously influence visitor satisfaction of Sepuluh November Museum. (2) Partially, Sense Experience and the Relate Experience significantly influence visitor satisfaction of Sepuluh November Museum, while the variable of Feel Experience, Think Experience, and Act Experience does not significantly influence visitor satisfaction of Sepuluh November Museum. (3) The five elements of Experiential Marketing variable that mostly influence the visitor satisfaction of Sepuluh November Museum is Sense Experience variable